Evaluation of Calyculin A Effect on γH2AX/53BP1 Focus Formation and Apoptosis in Human Umbilical Cord Blood Lymphocytes - Zastko, Lucián (Int J Mol Sci, 2021)
Dephosphorylation inhibitor calyculin A (cal A) has been reported to inhibit the disappearance of radiation-induced γH2AX DNA repair foci in human lymphocytes. However, other studies reported no change in the kinetics of γH2AX focus induction and loss in irradiated cells. While apoptosis might interplay with the kinetics of focus formation, it was not followed in irradiated cells along with DNA repair foci. Thus, to validate plausible explanations for significant variability in outputs of these studies, we evaluated the effect of cal A (1 and 10 nM) on γH2AX/53BP1 DNA repair foci and apoptosis in irradiated (1, 5, 10, and 100 cGy) human umbilical cord blood lymphocytes (UCBL) using automated fluorescence microscopy and annexin V-FITC/propidium iodide assay/γH2AX pan-staining, respectively. No effect of cal A on γH2AX and colocalized γH2AX/53BP1 foci induced by low doses (≤10 cGy) of γ-rays was observed. Moreover, 10 nM cal A treatment decreased the number of all types of DNA repair foci induced by 100 cGy irradiation. 10 nM cal A treatment induced apoptosis already at 2 h of treatment, independently from the delivered dose. Apoptosis was also detected in UCBL treated with lower cal A concentration, 1 nM, at longer cell incubation, 20 and 44 h. Our data suggest that apoptosis triggered by cal A in UCBL may underlie the failure of cal A to maintain radiation-induced γH2AX foci. All DSB molecular markers used in this study responded linearly to low-dose irradiation. Therefore, their combination may represent a strong biodosimetry tool for estimation of radiation response to low doses. Assessment of colocalized γH2AX/53BP1 improved the threshold of low dose detection.